In Between the Lines : Recent British Drawings - Lampert, Catherine; Cooper, Jeremy; Garrigues, Luce (London : Trinity Contemporary London, 2009)
Atkin, Kate ; Bowen, Siân ; Brooks, James ; Brown, Don ; Cattrell, Annie ; Curtis, Layla ; Dant, Adam ; Dixon, Jane ; Emin, Tracey ; Fairhurst, Angus ; Freud, Paul ; Greenhill, Joanna ; Grimes, Oona ; Gussin, Graham ; Haysom, Juliet ; Head, Tim ; Heath, Claude ; Hopkins, Louise ; Hughes, Dean ; Hume, Gary ; Landy, Michael ; McNally, Emma ; Musgrave, David ; Peri, Peter ; Prendergast, Kathy ; Richardson, Frances ; Shaw, George ; Shovlin, Jamie ; Talbot, Richard ; Turk, Gavin ; Turnbull, Alison ; Wilding, Alison ; Woodfine, Sarah ; Woolham, Simon
In Between the Lines : Recent British Drawings, Trinity Contemporary, London, 25 June - 10 July 2009
boek
Keywords: Groot-Brittannië